Fumigation-extraction method for the measurement of soil microbial biomass-S - Wu, J.; O'donnell, A.G.; He, Z.L.; Syers, J.K. (Soil biology & biochemistry, 1994)
Fumigation-extraction was evaluated for the measurement of microbial biomass-S in soil. Following fumigation in CHCl 3, S was extracted using 10 mM CaCl 2 at a soil-to-extractant ratio of 1-to-2 (w/v). These conditions were shown to be favourable in a range of soils containing extractable-S below 30 μg S g −1 soil. Extractable-S was measured by ion chromatography following H 2O 2 digestion. The increase in extractable-S following fumigation (the flush) was converted to biomass-S using a conversion factor ( k s) determined using 35S-labelled biomass-S. Using a soil-to-extractant ratio of 1-to-2 gave a value for K s of 0.31. This methodology was shown to be reliable for soils subject to arable, grassland or woodland management, with pH values above 3.7 and clay contents of 4–60%. The amounts of biomass-S measured in these soils were in the range 2.9–20 μg S g −1 soil. The data also showed that the amounts of biomass-S in soil are related to biomass-C and dependant upon soil management and fertilisation.